Characterization of wear rate of Al-12 wt%Si alloy based MMC reinforced with ZrO2 particulates - Nataraja M; G Balakumar; N Santhosh; M Rudra Naik (Materials Research Express, 2024)
The primary objective of this study is to fabricate an Al-12 wt% Si Alloy/ZrO _2 composite using the Stir Casting technique, with a specific focus on assessing its performance, particularly in terms of wear characteristics. This research presents a unique approach by utilizing Al-12 wt% Si Alloy as the matrix material, aiming to develop tailored Al Alloy matrix composites suitable for applications requiring enhanced tribological properties. The composites are systematically manufactured with varying percentages of micro-sized ZrO _2 reinforcements, specifically 0.5, 1, and 3 wt%. The incorporation of ZrO _2 results in significant improvements in wear resistance, a critical attribute for Al-12 wt% Si Alloy-based composites. These composites find extensive utility across industries such as marine, aerospace, automotive, and the power sector, where they are indispensable for producing vital components like electrical sliding contacts, gears, bearings, bushes, pistons, piston rings, and clutches. Despite the availability of various promising reinforcement materials, researchers persistently explore novel combinations of matrices and reinforcements to tailor properties and enhance cost-effectiveness. ZrO _2 has emerged as a notable reinforcement material in metal matrix composites, as evidenced by numerous research endeavours. The composites fabricated with ceramic reinforcement’s exhibit enhanced tribological characteristics. The study observes that the wear rate decreases up to 3 wt% of reinforcements, beyond which it increases due to reinforcement agglomeration. The optimal wear-resistant combination is found at 3 wt% of ZrO _2 , attributed to robust micro-coring and interstitial metal-oxygen bonding facilitated by the Si content in the Al-12%Si matrix. The results are further optimized using Response Surface Methodology (RSM) techniques and validated using the ANOVA table to elucidate the behaviour of the composites under different operational conditions. The hardness results further ascertain the decrease in the wear rate due to the inclusion of ZrO _2 reinforcements owing to micro coring and strengthening.